GENDER QUOTAS IN THE LEADERSHIP OF INTERNATIONAL COMPANIES: GLOBAL EXPERIENCE AND CHALLENGES (INNOVATIVE ECONOMY, 2025)
Shchutska D.I., Zastavnyi A.R. GENDER QUOTAS IN THE LEADERSHIP OF INTERNATIONAL COMPANIES: GLOBAL EXPERIENCE AND CHALLENGESPurpose. The aim of the article is to determine the peculiarities of implementing gender quotas in international companies, analyse their effectiveness and assess the risks and benefits. The objectives of the article are: to study the main approaches to the implementation of gender quotas in different countries, to conduct a comparative analysis of the effectiveness of quotas in the context of organisational and financial sustainability of companies, and to assess the risks and benefits of quotas in the corporate sector.Methodology or research. The study employs an interdisciplinary approach, utilizing the following methods: comparative analysis – examining different models of gender quota implementation across various countries and their outcomes; statistical analysis – evaluating the representation of women in corporate leadership and the impact of quotas on corporate efficiency; content analysis – reviewing legislative initiatives, academic studies, and reports from international organizations on the effectiveness of gender quotas; case studies – analysing successful and problematic cases of quota implementation in countries such as Norway, France, Germany, and the United States.Findings. It is established that global statistics for 2024 show a significant disproportion in the representation of men and women in leadership positions, with women holding only 31% of such positions. It was found that in profitable industries, in particular in finance and IT, the share of women in leadership positions is significantly lower than the global average. It is proved that the introduction of gender quotas in countries with legal obligations, such as Norway and France, contributes to a significant increase in the representation of women in management to 42% and 45%, respectively. It is analysed that in countries with a voluntary approach to gender quotas, such as Japan, the share of women in management positions remains low at 10 %. It is proved that the legislative consolidation of gender quotas is an effective tool for overcoming gender inequality in the top management of international companies. It is emphasised that voluntary initiatives without legal obligations have a limited impact on improving the gender balance in management.Originality. It is substantiated that gender quotas affect not only the social sphere but also provide economic benefits, which, unlike the existing approach, allows for a comprehensive assessment of their contribution to corporate efficiency. The understanding of the relationship between gender diversity in management and economic performance has been further developed, which contributes to the formation of new management strategies in international organisations. It analyses how different quota models influence financial performance, corporate reputation, and innovation levels. The research proves that companies with gender-balanced leadership demonstrate higher profitability and lower financial volatility.Practical value. The study’s findings can be used to develop recommendations for implementing gender quotas in the corporate sector. The analysis of different quota models' effectiveness can assist governments, business associations, and corporate executives in forming strategies to address gender imbalances. The research also emphasizes the need for a comprehensive approach, including training programs, mentorship initiatives, and monitoring systems to ensure quota effectiveness.Key words: gender quotas, gender quota system, corporate governance, gender parity, company management, international experience.
Keywords: gender quotas; gender quota system; corporate governance; gender parity; company management; international experience